PENGARUH PENGUNAAN MEDIA REALITA TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA SD - Ramadhayanti, Rizka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of the research is to analyse the effect of the use of realia media toward the students’ study result on the simple fraction in SDN 34 South of Pontianak on class 3. The method that has been used was experiment method with forms of quasi experimental research design in the stake non equivalent control group design. Research population of the entire grade 3A, 3B, 3C consists of 102 students in SDN 34 South of Pontianak. The research sample was a class sample that is class 3A (control) and class 3C (experiment class). Based on the result of data analysis, the median of post test in experiment class was 84,79 meanwhile the control class wa 75,24. The hypothesis test result using t-test (Polled Variance) with dk 62 on 5 % significant level as known as table t = 1,669 obtained count (table t = 1,669). Then Ha accepted and Ho rejected. It could be conclude that there is an influence of the us of realia media toward students’ study result on the simple fraction in SDN 34 South of Pontianak on class 3. The result of the calculation on the effect size in experiment class was 0,90 (high criteria). It means that the use of realia media gave high influence (effect) toward students’ study result on simple fractions in SDN 34 South of Pontianak on class 3. Keywords : Influence, Realia Media, Study Result